SYSTEMATIC LITERATURE REVIEW: PEMBELAJARAN IPA BERBASIS ETNOSAINS SEBAGAI STRATEGI PENGEMBANGAN KARAKTER CINTA LINGKUNGAN SISWA SEKOLAH DASAR - Dharmayanti, Luh Putri Diah; Lestari, Nyoman Ayu Putri (Pascasarjana Universitas Pendidikan Ganesha, 2025)
This study aims to evaluate the contribution of ethnoscience to Science Education (IPA) in fostering environmental awareness and love for nature among elementary school students. The method employed is a Systematic Literature Review (SLR) of thirty articles published between 2021 and 2025 retrieved from Google Scholar. The findings show that ethnoscience-based science learning effectively integrates local cultural values into classroom activities such as traditional product making, local agriculture, and the use of natural materials. Through these activities, students not only understand scientific concepts but also develop environmental care, responsibility, and pride in their local culture. However, several studies also identified challenges such as limited teacher knowledge and a lack of contextual learning resources. Overall, ethnoscience has proven effective in shaping environmental character and strengthening students’ cultural identity in elementary education.